Diferenciação curricular: análise da proposta de rotação por estações para estudantes no AEE nas SRMS - Obnesorg, Josiana Manuela da Silva (Universidade Estadual de Ponta Grossa (UEPG), 2026)
This dissertation analyzes contributions of the Station Rotation Pedagogical Approach, grounded in the principles of Universal Design for Learning (DUA in its Portuguese acronym), to curricular differentiation, engagement, and the development of students who are the target population of Special Education (PAEE – Portuguese acronym) served in Multifunctional Resource Rooms (SRM – Portuguese acronym) of a rural school. The study adopted a qualitative approach with a descriptive-analytical design and involved 21 students with different disabilities and three teachers from the Specialized Educational Support service (AEE – Portuguese acronym). Data were produced through structured questionnaires administered before and after the intervention, systematic observations, field notes, and documentary analysis, including school reports, Specialized Educational Support Plans, lesson plans, normative documents, and the Elementary and High School curriculum, in dialogue with the Brazilian National Common Core Curriculum (BNCC – Portuguese acronym). Data analysis was conducted using descriptive statistics and content analysis. Findings indicate that the proposal significantly enhanced student engagement, expanded opportunities for active participation, and contributed to the development of social, communicative, and organizational skills. The teachers reported noticeable advances in students’ autonomy, peer interaction, and involvement in activities, while also highlighting challenges related to the scarcity of pedagogical resources, limited time for individualized planning, and the need for greater institutional support. It is concluded that station rotation, when articulated with DUA principles and the specific demands of SRM, constitutes an effective pedagogical strategy for diversifying practices, promoting accessibility, and personalizing learning pathways. As an educational product, a guiding e-book was developed to support AEE teachers in implementing the proposal in different school contexts. Theoretical framework is grounded in Inclusive Education, drawing on contributions from Booth and Ainscow, and Mantoan and Sassaki, articulated with the Brazilian legal framework. The study was approved by the Research Ethics Committee (CAAE No 82191824.3.0000.0105) and was conducted within the scope of the student researcher’s activities as a member of the GEP-PROA Research Group at the State University of Ponta Grossa (UEPG), in the line of Curriculum, Accessibility, and Training.
Keywords: Educação Inclusiva; Salas de Recursos Multifuncionais; Rotação por Estações; Atendimento Educacional Especializado; Desenho Universal para a Aprendizagem